Explorations of Casco Bay by the U.S. Fish Commission in 1873. - Verrill, Addison Emery (Proceedings of the American Association for the Advancement of Science, 1874)
from the introduction: "[…] This year [1873], the party, which has been quite large, located at Peak's Island. This island is situated at the entrance of Portland Harbor, and about four miles from the city. This has proved to be a very favorable locality, on account of its central position, allowing us to dredge in all parts of Casco Bay and the connected bays and fiords, and to visit any of the numerous islands for which Casco. Bay is so famous, without too great loss of time ; and to take advantage of favorable weather for longer trips to the deeper waters outside the bay. The littoral animals of the island itself, owing to the diversity of the shores and purity of the water, have also proved to be numerous and interesting. The fishes and the investigations more immediately connected with the fisheries have been attended to by Prof. Baird, aided by his secretary, Mr. Rockwell, Prof. Theodore Gill, Dr. Edw. Palmer, Mr. G. Brown Goode, Mr. Spencer Biddle and others. The dredging operations, the examination of the food of fishes, and all investigations concerning the invertebrate animals generally, have been in charge of the writer and Mr. S. I. Smith […] "
World Polychaeta Database (WPolyDb). The article date is 1874, not 1873. Also available open access at Hathi https://hdl.handle.net/2027/uc1.b4248438?urlappend=%3Bseq=598